Morel-Lavallée Lesion: A not so rare, but often missed diagnosis - KTM Opdam; R van de Coevering; I van der Haven (Open Journal of Trauma - Peertechz Publications, 2017)
The Morel-Lavallée lesion is a closed, post-traumatic, soft tissue degloving injury. There is separation of the skin and subcutaneous tissue from the underlying fascia resulting in an effusion and creation of a perifascial space often containing lymph and necrotic fat. We present a case of a 70-year-old female that was referred to us with a painful right thigh after a fall from her bike. Ultrasound showed a persistent MLL and an ultrasound-guided injection with cortisone wasinjected the MLL, which resolved the patient's complaints. Level of evidence: Level 4.